Association between e-cigarette use and COVID-19 diagnosis: a systematic review and meta-analysis - Ying Xie; Xinmei Zhou; Dengmin Huang; Han Yao; Zheng Su; Zhao Liu; Anqi Cheng; Zhenxiao Huang; Jinxuan Li; Rui Qin; Yi Liu; Xin Xia; et al. (BMC Public Health)
Abstract Background The impact of e-cigarettes on COVID-19 remains unclear. This study aims to assess the relationship between e-cigarette use and COVID-19 diagnosis and other related outcomes. Methods This systematic review and meta-analysis searched studies from 2019 to April 2nd, 2024, in Medline (via OVID), EMBASE, Scopus and the Cochrane Central Register of Controlled Trials for eligible observational studies. Results Among the initially identified 1116 items, a total of 20 studies met the inclusion criteria. The meta-analysis revealed that e-cigarette use was significantly associated with higher odds of COVID-19 diagnosis (N = 14, adjusted odds ratio, OR 1.25, 95% confidence interval, CI 1.07 to 1.47, I2 = 62%). This association was more pronounced among the youth (N = 4, adjusted OR 1.78, 95% CI 1.17 to 2.72, I2 = 75%) and current e-cigarette users (N = 14, adjusted OR 1.30, 95% CI 1.10 to 1.55, I2 = 55%). Though the association was not significant among cohort or case-control studies at first, the robust results were shown excluding low-quality studies (N = 3, adjusted OR 1.25, 95% CI 1.03 to 1.50, I2 = 0%). The results remained consistent in leave-one-out analyses. Drawing from the available but limited research, no significance was observed between e-cigarette use or other COVID-19 outcomes including severe COVID-19, COVID-19-related death, symptoms or hospital admission. Heterogeneity and risk of bias should be noticed when explaining our results. Conclusions E-cigarette use was associated with an increased risk of COVID-19 diagnosis, particularly among youth and current users. Further high-quality evidence is needed to assess the overall health effects of e-cigarettes, with a particular focus on the youth and current users.